KESADARAN LINGKUNGAN DAN NILAI HIJAU YANG DIPERSEPSIKAN DALAM MEMBENTUK KEPUTUSAN PEMBELIAN UNTUK PERALATAN MAKAN DARI USAHA KERAJINAN PIRING PELEPAH PINANG DI DUMAI - Ika Apia Septira; Sabrina Siti Fadhilah; Christin Natalia Saragih (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the influence of environmental awareness and green perceived value on purchasing decisions for areca palm sheath tableware products in Dumai. The study employed a quantitative approach with an explanatory research design. The sampling technique used was purposive sampling involving 100 respondents. Data were collected through questionnaires using a Likert scale and analyzed using IBM SPSS Statistics. The results showed that environmental awareness did not have a significant effect on purchasing decisions, with a t-value of -1.078 and a significance value of 0.284 > 0.05. Meanwhile, green perceived value had a positive and significant effect on purchasing decisions, with a t-value of 6.129 and a significance value of 0.000 < 0.05. Simultaneously, environmental awareness and green perceived value significantly influenced purchasing decisions, as indicated by an F-value of 18.832 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) was 0.280, indicating that the independent variables explained 28.0% of the variation in purchasing decisions, while the remaining 72.0% was influenced by other factors outside this study. The findings indicate that green perceived value is the dominant factor influencing consumers’ purchasing decisions toward environmentally friendly tableware products made from areca palm sheath